Creating Family Independence with Medicinal Plants and Plant Information Cards: Empowering the Puntukdoro Community in an Effort to Preserve Traditional Medicine - Purwanta; Puput Dinul Chotimah; Brina Oktasahara; Brilian Arya Sena (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Taman obat keluarga (TOGA) are a collection of plants that play an important role in traditional medicine and have properties that enhance health. The diversity of medicinal plants offers a more economical alternative compared to modern medicines. Seeing the increasing potential of medicinal plants in traditional medicine, the community has started planting them in their yards to facilitate access when needed. However, in Puntukdoro Village, most of the community only knows medicinal plants as cooking spices Apart from that, the obstacles faced are limited land. Based on the aforementioned issues, the presence of vacant land in Puntukdoro Village, the Kuliah Kerja Nyata (KKN) team serving in Puntukdoro Village, namely Universitas Gadjah Mada, Universitas Brawijaya, and Institut Agama Islam Negeri Ponorogo, will renovate the vacant land into a TOGA to enhance the aesthetic value of the area. Additionally, the Kuliah Kerja Nyata (KKN) UGM team offers a solution in the form of educating the community by installing plant information cards integrated with Quick Response (QR) code features containing information such as planting methods, maintenance processes, harvest times, and the benefits of the plants. The creation of this garden aims to empower the Puntukdoro community to preserve traditional medicine. This program will take place from July to August 2024, divided into several stages starting from preparation, implementation, evaluation, and program sustainability. The outcomes of this activity include garden design creation, land arrangement, planting, maintenance, installation of plant information cards, as well as evaluation and sustainability discussions covering several aspects, such as land condition, plant growth condition, and duty schedule creation. With the existence of this program, it is hoped that the community can integrate knowledge about medicinal plants into daily life and can initiate the community to plant medicinal plants in their home yards so that the preservation of traditional medicine can be applied in every family and the quality of health can improve.